Congenital Urethral Anomalies in Boys. Part I: Posterior Urethral Valves - Abdolmohammad Kajbafzadeh (Urology Journal, 2005)
Introduction: The aims of this review are one, to consider that congenital urethral anomalies are not a simple disease entity in all patients. This is accomplished by reviewing the evidence for presence of posterior urethral valve subtypes and comorbidity of various unexplained clinical conditions in some children leading to chronic renal failure. The review’s second aim is to describe the effects of fetal lower urinary tract obstruction on postnatal bladder function and the consequence of bladder dysfunction on the remaining postnatal renal function. Materials and Methods: The literature was extensively reviewed concerning the different types of congenital urethral outlet obstruction presentations, diagnosis, and different types of treatment modalities, morbidity, mortality, and new concepts for this old problem. These findings were compared with conventional approaches to these anomalies. The 739 published papers on posterior urethral valves were evaluated, and a quarter of those are addressed. All radiologic presentations and figures in this review were selected from among the records of Iranian patients treated by the author during the last 25 years. Results: A significant overlap of presentation before antenatally diagnosed era was observed. The natural history of these anomalies is becoming clear and the hypothesis of posterior urethral diaphragm is popular among several investigators in comparison to the original valves classification by Young in 1903. Conclusions: Further molecular investigation of the urinary tract is needed to better understand the pathophysiology of renal and bladder function in children who are born with antenatally diagnosed congenital urethral obstruction. These anomalies must be treated by urologists with a vast experience with valves and other rare congenital urethral anomalies.